Chemical Composition of Aerosols of an Electronic Cigarette - Wen-Hsi Cheng; Chia-Yu Chang; Yi-Ya Chen; Hui-Wen Su (Aerosol and Air Quality Research)
Abstract A needle trap sampler (NTS) packed with 60–80-mesh divinylbenzene (DVB) adsorbent inside a 22-gauge stainless steel needle was used as a micro sampling device to extract chemical compounds in electronic cigarette (e-cigarette) aerosol. The samples were then analyzed using gas chromatography (GC)-mass spectroscopy (MS) to determine the constituents. Based on the experimental results, e-cigarette smokers are exposed to high concentrations of nicotine (146 ± 51 mg m−3) during long sessions. If the e-cigarette liquid leaks though the filter of the cartridge, the user is exposed to even greater quantities (914 mg m−3). However, the secondhand aerosol contains less than 1 mg m−3 of nicotine on average (with 0.43–1.74 mg m−3 being the approximate full range). In addition to nicotine, the airborne emissions from e-cigarettes mainly consist of vegetable glycerin, propylene glycol, and triacetin.